Ocular Surface Cytotoxicity and Safety Evaluation of Tafluprost, a Recently Developed Anti-Glaucoma Prostaglandin Analog. (January 2014) - Niwano, Yoshimi; Iwasawa, Atsuo; Ayaki, Masahiko
In vitro cytotoxicity of tafluprost, which is the most recently developed anti-glaucoma prostaglandin (PG) analog, in ocular surface cells is addressed in comparison with other PG analogs. Irrespective of cell lines and models, the cytotoxicity of anti-glaucoma PG eyedrops was primarily related to the concentration of benzalkonium chloride (BAK) contained in the eyedrops as a preservative. Accordingly, preservative-free tafluprost was apparently less cytotoxic than BAK-preserved PG analogs. Furthermore, our study for cytotoxicity assays on ocular cells, conducted by comprehensive investigations covering a variety of concentrations and treatment times, which is termed the cell viability score (CVS) system, demonstrated that 0.001% BAK-preserved tafluprost was not cytotoxic, and suggested that tafluprost may even reduce the cytotoxic effect of BAK. It has been reported that adverse reactions associated with tafluprost in healthy human volunteers and patients with glaucoma include conjunctival hyperemia, eyelid pigmentation, eyelash bristles, and deepening of upper eyelid sulcus. Nonetheless, most clinical studies have demonstrated that not only preservative-free tafluprost but also BAK-preserved tafluprost is well tolerated and safe in patients with glaucoma and ocular hypertension.